Role of Forensic Evidence in the Criminal Trials; A Legal Analysis in Pakistan Perspective - Amir Aleem Saddique; Muzzammil Hussain; Mohsan Iqbal; Bilal Ahmad (Research Journal of Psychology, 2024)
This research analyze how Forensic evidence impacts the criminal justice setup in Pakistan. It delves into the types of forensic evidence used, in the way that DNA profiling, fingerprint study, ballistics, and digital forensics, and explores their request in high-profile cases like the Zainab Ansari case and the Benazir Bhutto assassination. The study too highlights the function of forensic specialists in trials and the important impact of forensic evidence on trial effects, containing embellishing veracity and barring illegal confidences. The paper recognizes various challenges faced in the productive use of forensic evidence in Pakistan, containing old-fashioned supplies, lack of patterned processes, source restraints, and lacking preparation for permissible pros. It again discusses the legal and uniform structure commanding forensic evidence, noticing that while organizations like the Punjab Forensic Science Agency have created important tramps, there are still gaps that need to be addressed. Key pieces of advice for reconstructing the use of forensic evidence contain renovating the permissible foundation, investing in up-to-date technology, extending forensic assistances, and improving preparation for forensic specialists and legal experts. The research underlines the need for public knowledge campaigns to build count on forensic skill and desires that future studies should devote effort to something approximate analyses with additional nations, the impact of concerning details progresses, and public understanding of forensic evidence. By addressing these issues, the unification of forensic evidence into Pakistan's criminal justice setup maybe considerably enhanced, superior to more trustworthy and just consequences in criminal trials.